Harmonic Surface Mapping Algorithm for Electrostatic Potentials in an Atomistic/Continuum Hybrid Model for Electrolyte Solutions (Communications in Computational Physics, 2020)
Simulating charged many-body systems has been a computational demanding task due to the long-range nature of electrostatic interaction. For the multi-scalemodel of electrolytes which combines the strengths of atomistic/continuum electrolyterepresentations, a harmonic surface mapping algorithm is developed for fast and accurate evaluation of the electrostatic reaction potentials. Our method reformulates thereaction potential into a sum of image charges for the near-field, and a charge densityon an auxiliary spherical surface for the far-field, which can be further discretized intopoint charges. Fast multipole method is used to accelerate the pairwise Coulomb summation. The accuracy and efficiency of our algorithm, as well as the choice of relevantnumerical parameters are demonstrated in detail. As a concrete example, for chargesclose to the dielectric interface, our method can improve the accuracy by two orders ofmagnitudes compared to the Kirkwood series expansion method.
Keywords: Multi-scale modeling; linearized Poisson-Boltzmann equation; Green's function; Harmonic surface mapping; image charges.